UPLC–MS/MS study of the effect of dandelion root extract on the plasma levels of the selected irreversible tyrosine kinase inhibitors dasatinib, imatinib and nilotinib in rats: Potential risk of pharmacokinetic interactions. (1st September 2019) - Alzoman, Nourah Z.; Maher, Hadir M.; Shehata, Shereen M.; Abanmy, Norah O.
Abstract: Tyrosine kinase inhibitor treatments for chronic myeloid leukaemia based on nilotinib (NIL), dasatinib (DAS) and imatinib (IMA) have improved patient quality of life and have turned chronic myeloid leukemia from a fatal disease into a chronic disease. Dandelion is a rich source of phenolic compounds with strong biological properties, and the effects of using this plant in the treatment of different illnesses can be linked to the presence of various polyphenols found in the different parts of the plant. Thus, dandelion can potentially be used as a nutraceutical (dietary antioxidant) to prevent different disorders associated with oxidative stress, i.e. cardiovascular disorders, cancer and inflammatory processes. Mutual interference between a drug and a food constituent may result in altered pharmacokinetics of the drug and undesired or even dangerous clinical situations. In the present study, a bioanalytical ultra performance liquid chromatography–tandem mass spectrometer (UPLC–MS/MS) method was developed and validated for the quantification of DAS, IMA and NIL in rat plasma. Sample preparation was carried out using solid‐phase extraction with C18 cartridges with a good extraction recovery of ≥94.37% for the three drugs. The method was fully validated as per the US Food and Drug Administration guidelines.